The dynamics of patriarchy as a cultural system in the social life of arab communities - Yasmin Mumtaza; Yuniar Mujiwati; Adi Nur Aziz (Journal of Law Science, 2026)
This study examines patriarchal culture as a dynamic cultural system among the Arab ethnic community in Kebonsari Village, Pasuruan City, comparing their perspectives and experiences with those of the surrounding non-Arab community. Using a comparative case study design grounded in Walby's (1990) theory of patriarchy, this study employed semi structured interviews and non-participant observation with 13 purposively sampled informants across three categories: household heads, married women, and the younger generation. Findings show that patriarchal authority operates unevenly across Walby's structures: the domestic sphere has undergone the most visible renegotiation, with joint decision-making replacing unilateral male authority, while culture remains the most stable structure, sustained through religious and lineage-based norms. Paid employment proves selectively restricted: women gain financial independence yet remain constrained in formal employment. Notably, variation in parental control over daughters' mobility appears as pronounced within the Arab community itself as between Arab and non-Arab groups, indicating that the persistence of patriarchal culture cannot be explained by ethnicity alone. These findings extend prior research on Indonesian patriarchal culture beyond textual and family level analyses, and offer policymakers an empirical basis for developing culturally responsive, rather than uniform, gender-equality programs.